DIRECTIONS OF COOPERATION BETWEEN UNIVERSITY AND SCIENTOMETRIC INFORMATION SYSTEMS – MONITORING, RESEARCH ANALYSIS AND PUBLICATIONS INDEXING OF UNIVERSITIES - Vasilyev, Oleksii V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The paper examines scientometric information systems in functioning of university.